WordPerfect 4.2 : procedures manual - Curtin, Dennis P. (New Jersey : Prentice-Hall, 1989)
This manual is a complete guide to wordperfect 5.0. It is organized into fifty topics that cover, step, basic, and advanced word processing procedures.
1. Introduction to the computer and BASIC -- 2. Top-down program design and structured programming -- 3. Rules and procedures for using basic -- 4. LET, PRINT, TAB Function, SPC Function, END and REM Statements -- 5. Input, output, and termination statements -- 6. Control statements -- 7. Arrays -- 8. Functions -- 9. Subroutines -- 10. Sequential file processing.
Includes index.
Keywords: BASIC (COMPUTER PROGRAM LANGUAGE)